Here N There Pencil Case / Razia Abdul Rahman - Abdul Rahman, Razia (2020)
The business is based on partnership where it consists of 5 people which hold important positions in the company such as General Manager, Administration Manager Marketing Manager, Operational Manager and Financial Manager. The business capital is RM 50 000. Here n There case is an innovative pencil case. Many people like to bring books everywhere with them. They also bring along pencil to write down anything. However, existing pencil case is commonly very big. To bring along pencil without protection or storage system is not an option because it can damage the pencil. Here n There case is a small and lightweight pencil case that can be attached to a book. It also serves as pencil holder Here n There target market are white-collars workers and students. White-collars workers usually will have meeting every now and then and they need to be prepared. This product will make it convenient for them to go to urgent meeting. Same goes to student who use books and pencil every day. Seremban is chosen as our business location as it has abundant of companies and school. There are no other pencil case that serve this function in the market currently. With the multipurpose use, it can attract many people to the product. With innovative and top quality product, we believe our business will always be customer’s first choice.